Examining the Effect of Age on Visual–Vestibular Self-Motion Perception Using a Driving Paradigm. (May 2017) - Ramkhalawansingh, Robert; Keshavarz, Behrang; Haycock, Bruce; Shahab, Saba; Campos, Jennifer L.
Previous psychophysical research has examined how younger adults and non-human primates integrate visual and vestibular cues to perceive self-motion. However, there is much to be learned about how multisensory self-motion perception changes with age, and how these changes affect performance on everyday tasks involving self-motion. Evidence suggests that older adults display heightened multisensory integration compared with younger adults; however, few previous studies have examined this for visual–vestibular integration. To explore age differences in the way that visual and vestibular cues contribute to self-motion perception, we had younger and older participants complete a basic driving task containing visual and vestibular cues. We compared their performance against a previously established control group that experienced visual cues alone. Performance measures included speed, speed variability, and lateral position. Vestibular inputs resulted in more precise speed control among older adults, but not younger adults, when traversing curves. Older adults demonstrated more variability in lateral position when vestibular inputs were available versus when they were absent. These observations align with previous evidence of age-related differences in multisensory integration and demonstrate that they may extend to visual–vestibular integration. These findings may have implications for vehicle and simulator design when considering older users.